Puzzle: Vintage Kellogg's - The Jigsaw Puzzle Factory, LLC (North Andover, MA The Jigsaw Puzzle Factory)
(3z(BThis Kellogg's puzzle shows vintage Kellogg cereal boxes - Corn Flakes, All-Bran.s Distributor's website
Keywords: Advertising Kellogg's cereals